Design and Analysis of Satellite Internet Simulation and Verification System for Space Remote Sensing Services - Ying TAO; Wei LIU; Lei ZHANG; Zihe GAO; Na ZHOU (天地一体化信息网络)
The architecture of satellite Internet composed of LEO satellites with remote sensing/inter-satellite and satellite-earth networking, on-board edge computing functions, and ground cloud computing centers, and various types of terminals such as sky, near space, space, ground, sea terminals was put forward.The functional architecture of on-board edge computing, included resource layer, virtualization layer, service layer, service management layer and application layer was given.On the basis of proposed the construction method of on-board edge computing simulation and verification system, a satellite Internet simulation and verification system serving space sensing services was designed, and space-based sensing information processing and distribution experiments were carried out.According to the comparison of network resource occupation and user service delay with different information processing and distribution methods, the capability level of satellite Internet for space sensing services under different capability conditions were analyzed.